Diversity Analysis of Streptomycetes and Associated Phosphotranspherase Genes in Soil - Laskaris, Paris; Sekine, Takuya; Wellington, Elizabeth M. H. (PLOS ONE, 2012)
An attempt was made to verify the observation that Streptomyces griseus was prevalent in soil based on isolation work. A genus-specific PCR was developed for Streptomyces based on the housekeeping gene atpD and used to investigate species diversity within selected soils. The presence of S. griseus was investigated to determine coexistence of resistance-only streptomycin phosphotransferase (strA) in the same soil as streptomycin producers. Two additional PCR-based assays were developed; one specific for strA in association with production, the other for more diverse strA and other related phosphotranferases. Both the S. griseus atpD and strA genes were below the PCR detection limit in all soils examined. A number of more diverse phosphotransferase genes were amplified, a minority of which may be associated with streptomycin production. We conclude that neither streptomycin producers nor S. griseus are prevalent in the fresh or chitin and starch-amended soils examined (less than 0.1% of soil actinobacteria). One of the soil sites had received plantomycin (active ingredient: streptomycin) and diversity studies suggested that this altered the streptomycete populations present in the soil.